Comparison study on the impact compression mechanical properties of coral aggregate concrete and ordinary Portland concrete. (October 2022) - Cai, Yang; Ren, Hui-qi; Long, Zhi-lin; Guo, Rui-qi; Du, Kuang-min; Chen, Sha-sha; Zheng, Zhi-hao
Abstract: Coral aggregate concrete (CAC) has been widely used in the construction of South Sea islands and reefs. However, the dynamic mechanical properties of CAC under high strain rate loading are rarely reported. This study aims to compares the mechanical properties of CAC and ordinary Portland cement concrete (OPC). A 100 mm-diameter split Hopkinson pressure bar (SHPB) was used to perform an impact compression loading test on CAC and OPC. The dynamic mechanical properties of CAC were assessed in terms of the failure pattern, particle evolution after failure, dynamic increase factor ( DIF ), brittleness analyses and impact toughness. The results show that the failure plane of CAC directly penetrates the coral aggregate, unlike OPC, which has an interfacial transition zone (ITZ). When the strain rate reaches 166 s −1, the evolution of the particle size after CAC breaks basically becomes stable compared with that after OPC breaks. Under the same strain rate, the DIF value of CAC is higher than that of OPC. An empirical equation is proposed for the estimation of the DIF of CAC based on the experimental results. A significant influence of the strain rate on the dynamic elastic modulus of CAC was observed. Moreover, a method for evaluating the brittleness of concrete under dynamic loading is proposed. At a strain rate of 10 -5 -166 s −1, comparing with OPC materials shows that there is an obvious brittle-ductile transition in CAC materials. The impact toughness of CAC is significantly lower than that of OPC, and the energy absorbed by CAC before crushing is significantly less than that absorbed by OPC.